EFFECTS OF AN INTENSE PHYSICAL ACTIVITY PROGRAM ON THE BLOOD PRESSURE AND HEART RATE OF 12-15-YEAR-OLD ADOLESCENTS - López Sánchez, Guillermo Felipe (2016)
Introduction and objective: research focused on the improvement of cardiovascular health is very important nowadays. This paper focuses on studying the effects of a physical activity program on the blood pressure and heart rate of a group of adolescents. Method: This investigation involved 38 adolescents (14 males and 24 females), ages between 12 and 15 years old (average age 13.61 and standard deviation 1.00). The variables considered were: blood pressure (systolic and diastolic) and resting heart rate. Blood pressure and heart rate were measured by a Visomat Comfort 20/40 arm sphygmomanometer. The procedure was as follows: pre-test, intervention and pos-test. The intervention consisted of 3 days per week of high-intensity physical activity, 15 minutes per day, during 12 weeks. Results: Data was analyzed through the SPSS 22 and significant improvements were obtained in blood pressure and heart rate (Sig <0.05). Conclusions: The physical activity program implemented in this study is a useful tool to improve blood pressure and heart rate in adolescents.